Investigation of ultra-high sensitivity klystron cavity transducers for broadband resonant-mass gravitational wave detectors. - Guilherme Leite Pimentel (2008)
We show that, with a suitable choice of the parameters of the gravitational wave detector Mario Schenberg, with technological accessible parameters (using state-of-art electronics), its sensitivity curve can be improved over the current project curve to become competitive with interferometric detectors in a frequency band of ~1500 Hz, in the region from 1000 to 10000 Hz (these competitive bands are centered at the sphere's quadrupole modes). The sensitivity curve of an array of 100 identical spheres identical to the Schenberg one is also analyzed, and is competitive against advanced LIGO in the entire band. A detailed study of the project's viability is conducted, with an emphasis on the project of the klystron resonant cavity, which will have a center post with a 1 nm gap, which represents a great technological challenge. This challenge is analyzed in terms of the cavity project as well as with a focus on the Casimir effect on the cavity. This could open an opportunity for precise measurements of this effect on a new distance scale compared to current measurements (in the m scale).